Functional characterization of E2F3b in human HepG2 liver cancer cell line. Issue 4 (26th December 2017) - Lu, Yujia; Li, Wei
Abstract: E2F3 is a transcription factor that has been shown to be overexpressed in hepatocellular carcinoma (HCC). It is well‐known that the E2F3 gene encodes two proteins E2F3a and E2F3b. Therefore, the functions of the two distinct isoforms need to be clarified separately. To characterize the function of E2F3b in HCC, the effects of ectopic expression of E2F3b on cell proliferation, cell cycle, apoptosis and gene expression were investigated. E2F3b promoted G1/S phase transition and markedly increased cell proliferation, but had minor effect on apoptosis. Microarray analyses identified 366 differentially expressed genes (171 upregulated and 195 downregulated) in E2F3b‐ overexpressing cells. Differential expression of 16 genes relevant to cell cycle and cell proliferation were further verified by real‐time PCR. Six genes, including CDC2, CCNE1, ARF, MAP4K2, MUSK, and PAX2 were confirmed to be upregulated by more than twofold; one gene, CCNA2 was validated to be downregulated by more than twofold. We also confirmed that E2F3b increased the protein levels of both cyclin E and Arf but did not affect cyclin D1 protein. These results suggest that E2F3b functions as an important promoter for cell proliferation and plays important roles in transcriptional regulation in HepG2 liver cancer cells. Abstract : E2F3b is one of the two isoforms encoded by E2F3 gene. Functional study showed that E2F3b promoted G1/S phase transition and markedly increased cell proliferation, but had minor effect on apoptosis. E2F3b significantly upregulated CCNE1 and Arf on both mRNA and protein levels.